2017
DOI: 10.1111/jan.13485
|View full text |Cite
|
Sign up to set email alerts
|

Structured nurse‐led follow‐up for patients after discharge from the intensive care unit: Prospective quasi‐experimental study

Abstract: The structured nurse-led follow-up did not reveal an effect on the intensive care patients studied. Further examination of intensive care nurse-led follow-up is needed, taking into account the heterogeneity of the patient population, variations in length of ward stay, patients' health care needs during the first week at home after discharge from general ward and health status before intensive care admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 31 publications
(53 reference statements)
0
36
0
Order By: Relevance
“…According to Palesjö et al (2015), patients might need help to reflect on such memories together with nurses from the ICU, who also are capable of answering these experiences. Recently, Jonasdottir, Jones, Sigurdsson, and Jonsdottir (2018) found that structured nurse-led follow-up did not improve patients' health status compared with usual care; they argued for even more extensive tailoring of individual needs during an ICU follow-up because of the heterogeneous group of patients. We argue that an increased awareness of the patient's situation during transfers may help nurses meet such specific memories during follow-up visits, and this is an area for future research in relation to ICU follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…According to Palesjö et al (2015), patients might need help to reflect on such memories together with nurses from the ICU, who also are capable of answering these experiences. Recently, Jonasdottir, Jones, Sigurdsson, and Jonsdottir (2018) found that structured nurse-led follow-up did not improve patients' health status compared with usual care; they argued for even more extensive tailoring of individual needs during an ICU follow-up because of the heterogeneous group of patients. We argue that an increased awareness of the patient's situation during transfers may help nurses meet such specific memories during follow-up visits, and this is an area for future research in relation to ICU follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies had different study designs: two studies were RCTs, 32,33 one was a block intervention study, 34 one had a pretestepost-test control group design, 35 and one was a non-RCT. 36 Walsh et al 32 and Bench et al 33 published their study protocol separately. 37,38 The studies were conducted in Australia 34,35 and Western Europe 32,33,36 (see Table 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…36 Walsh et al 32 and Bench et al 33 published their study protocol separately. 37,38 The studies were conducted in Australia 34,35 and Western Europe 32,33,36 (see Table 1). All studies included adult ICU patients.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations